Contact Dermatitis and Chemical Sensitivity among Ceramics Workers - Rachel E. Tao; Jessica N. Pixley; Steven R. Feldman (Journal of Dermatology and Dermatologic Surgery)
Background: Contact dermatitis comprises 90%–95% of occupational skin disease cases in the United States. Some of these cases occur in ceramics workers who are in direct and prolonged contact with clays, glazes, and pastes that may cause allergic contact dermatitis (ACD) and irritant contact dermatitis (ICD). Purpose: Our objective is to characterize the frequency of ACD and ICD among ceramics workers and to describe the culprit chemicals reported to cause chemical sensitization and positive patch test results. Methods: A literature review was performed in PubMed between February and July 2023 using the following keywords: “ceramics,” “potter,” “clay,” “eczema,” “hand dermatitis,” “atopic dermatitis,” and “glaze.” Twenty-seven articles were reviewed, of which nine were reports of contact dermatitis in ceramics workers written in English and were included in this review. The positive contactants were reviewed for presence in the ACDS Core Allergen Series and the T.R.U.E® Test series. Results: Of the 435 ceramics workers, 23% had active hand dermatitis. Of the ceramics workers with active hand dermatitis, 55% had ACD and 45% had ICD. Of the 52 sensitizing substances, 36 were not present in either of the two patch-testing series evaluated. Conclusion: In cases where potential culprit allergens may be difficult to identify for the purpose of patch testing, direct application of the clay body or glaze may be performed. Including these chemical allergens in routine patch testing series could facilitate better outcomes for ceramics workers with dermatitis.